Representações sociais de uma ferrovia : um estudo de caso sobre os maquinistas da estrada de ferro Vitória a Minas - Oliveira, Ubiratan Correa Ribeiro de (2006)
The present dissertation investigates the social representation of a railroad with great historic expression and strong regional characteristics, under the view of some class of workers, the engineers. Considering its initial proposal, the main goal is to